2019
DOI: 10.3767/blumea.2019.64.03.01
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Scleria (Cyperaceae) in Madagascar

Abstract: A taxonomic revision of the genus Scleria (Cyperoideae, Cyperaceae) in Madagascar is presented. Herbarium specimens have been examined and 422 identified to species level. Our results recognise 25 species of Scleria from Madagascar, plus an additional heterotypic variety. Eight species are endemic to Madagascar, two are near endemic, eight taxa are also found on mainland Africa, and eight are widespread tropical taxa. Scleria achtenii is reported from Madagascar for the first time, and S. rosea is accepted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For a description and notes on the genus, see Goetghebeur (1998). For infrageneric classification and recent taxonomic treatments, see Bauters et al (2016, 2018, 2019), Bauters (2018), and Galán Díaz et al (2019).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…For a description and notes on the genus, see Goetghebeur (1998). For infrageneric classification and recent taxonomic treatments, see Bauters et al (2016, 2018, 2019), Bauters (2018), and Galán Díaz et al (2019).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Nine species are endemic to Madagascar, mostly restricted to the tropical montane forests. Scleria section Abortivae includes five species endemic to Madagascar and the western Indian Ocean islands (Galán Díaz et al., 2019). Two other genera include a significant number of endemic species: Bulbostylis and Schoenoplectiella .…”
Section: Discussionmentioning
confidence: 99%
“…Distribution data were obtained from Govaerts et al. (2020) and recent literature (Galán Díaz et al., 2019; Larridon et al., 2019). Biogeographical analyses were carried out in the R (R Core Team, 2019) package BioGeoBEARS (Matzke, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Most species occur in tropical areas but some occupy more temperate climatic regions (Larridon et al 2021b). Scleria is a functionally diverse genus that includes annual and perennial herbs, the latter often using stoloniferous rhizomes or tubers (Bauters et al 2016; Galán Díaz et al 2019). Recent studies have disentangled the evolutionary relationships among Scleria species (Bauters et al 2016, 2018) and identified major dispersal and niche shift events (Larridon et al 2021b).…”
Section: Introductionmentioning
confidence: 99%